Exploring Challenges and Motivations of Female Married Undergraduate Students English Department, Msllata (Al-Qalaa Journal, 2024)
This research on “Exploring the Challenges and Motivations of Female Married Undergraduate Students English Department, Msllata" analyses the problems encountered by the respondents (married students) in their pursuit of a college degree. Such challenges are relative to the family the college and to the Libyan society and culture. Furthermore, it recounts the reasons /motivations of these students in wanting to achieve an education. Frequency counts, percentage and ranks are used to interpret and analyze the results of the survey collected from these respondents. Findings proves that the paramount challenge emanated from the duality or multiplicity of roles that these respondents performed. Nonetheless, despite these obstacles, their desire to obtain a degree has inspirited them to persevere. In the end, the quality of determination and persistence in the face of such obstacles has defined these respondents as responsible wives and mothers and students.